CtCake Ordering System - Nordin, Aqilah; Abdul Jalil, Rozita (Applied Information Technology And Computer Science, 2026)
The bakery industry increasingly relies on technology to enhance customer experience and operational efficiency, particularly in managing custom orders. At Ct Cake Silaturahim, a home-based bakery in Ipoh, Perak, orders are managed manually via WhatsApp, Instagram, and agents, resulting in inefficiencies such as delayed responses, missed bookings, and limited capacity to analyze customer feedback. To address these challenges, this research focuses on developing a web-based ordering system, CtCake, to centralize and streamline order management processes. Using the Prototyping Methodology, the system was iteratively designed and developed with feedback from stakeholders to ensure it meets business needs. Core functionalities include a user-friendly interface for browsing and ordering cake, QR code payment, and tools for collecting and analyzing customer feedback. Data flow diagrams and entity relationship diagrams guided the design, while MySQL was employed to implement the database. The results demonstrate significant improvements in order accuracy, customer satisfaction, and operational efficiency. The system reduces response time, minimizes errors, and provides actionable insights through data analytics. In conclusion, the CtCake system enhances the ability to manage orders efficiently and positions the business for sustainable growth by fostering improved customer engagement and operational excellence.